When the Levee Breaks: Black Migration and Economic Development in the American South - Hornbeck, Richard; Naidu, Suresh (American Economic Review, 2014)
In the American South, postbellum economic development may have been restricted in part by white landowners' access to low-wage black labor. This paper examines the impact of the Great Mississippi Flood of 1927 on black out-migration and subsequent agricultural development. Flooded counties experienced an immediate and persistent out-migration of black population. Over time, landowners in flooded counties modernized agricultural production and increased its capital intensity relative to landowners in nearby similar non-flooded counties. Landowners resisted black out-migration, however, benefiting from the status quo system of labor-intensive agricultural production. (JEL J15, J43, N32, N52, N92, Q54, R23)